2016
DOI: 10.1152/ajpcell.00230.2015
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulfide promotes angiogenesis by downregulating miR-640 via the VEGFR2/mTOR pathway

Abstract: We previously found hydrogen sulfide (H2S) to be a new proangiogenic factor. However, the mechanisms underlying the cardiovascular effect of this small gas molecule remain largely unknown. The aim of the present study was to identify the essential microRNAs (miRNAs) involved in the transduction of H2S signals in vascular endothelial cells (ECs). The expression of miR-640 and its signaling elements, vascular endothelial growth factor receptor 2 (VEGFR2), hypoxia inducible factor 1-α (HIF1A), and mammalian targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 34 publications
1
41
0
1
Order By: Relevance
“…In addition to this, further study has demonstrated that H 2 S specifically disrupts cys1045-cys1024 disulfide bond in vascular endothelial growth factor receptor 2 (VEGFR2) and then stimulates its conformation for angiogenesis (Tao et al, 2013). As a molecular switch, H 2 S is also reported to activate signal transducer and activator of transcription 3 (STAT3) (Kan et al, 2014), mammalian target of rapamycin (mTOR), and the VEGFR2 pathway (Zhou et al, 2016), then the endothelial cell proliferation and angiogenesis are observed. It is noteworthy that FIGURE 3 | Schematic illustration of the underlying mechanisms of H 2 Sinduced angiogenesis.…”
Section: Regulation Of Endothelial Function By H 2 S Under Physiologimentioning
confidence: 92%
“…In addition to this, further study has demonstrated that H 2 S specifically disrupts cys1045-cys1024 disulfide bond in vascular endothelial growth factor receptor 2 (VEGFR2) and then stimulates its conformation for angiogenesis (Tao et al, 2013). As a molecular switch, H 2 S is also reported to activate signal transducer and activator of transcription 3 (STAT3) (Kan et al, 2014), mammalian target of rapamycin (mTOR), and the VEGFR2 pathway (Zhou et al, 2016), then the endothelial cell proliferation and angiogenesis are observed. It is noteworthy that FIGURE 3 | Schematic illustration of the underlying mechanisms of H 2 Sinduced angiogenesis.…”
Section: Regulation Of Endothelial Function By H 2 S Under Physiologimentioning
confidence: 92%
“…Similarly, in rat brain capillary endothelial cells incubation with a H 2 S donor, promoted an increase in HIF-1α and VEGF mRNA and protein levels, and enhanced HIF-1 DNA binding [48]. In cells treated with a H 2 S donor, angiogenic responses were linked to miR-640 down regulation and mediated by a VEGFR2/mTOR/HIF-1α pathway [49]. However, it should be kept in mind that under certain conditions H 2 S donors have been shown to suppress HIF-1 [50].…”
Section: Hypoxia and H2smentioning
confidence: 99%
“…Recently, we also reported that the expression of 12 miRNAs in HUVECs were changed after administration of NaHS using an Affymetrix gene chip expression assay. Among these miRNAs, miR-640 is down-regulated and regulates the stability of hypoxia-inducible factor 1 alpha (HIF1A) mRNA14. Considerable evidence has been provided to support the central role of eNOS in regulating endothelial cell functions such as migration24.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous microarray data has shown that H 2 S could increase the level of miR-455-3p in HUVECs14. Plasma miR-455-3p has been reported to serve as a potential biomarker for abdominal aortic aneurysm15.…”
mentioning
confidence: 98%